Do bystanders always see more than the players? Exploring Solomon’s paradox through meta-analysis - Lin, Hongyi; Zheng, Hong; Wang, Fengyan (Frontiers in Psychology, 2023)
Solomon’s paradox is a widespread phenomenon regarding how we think, which asserts that people reason more wisely about other people’s social problems than they do about their own. This means that we are more likely to make rational decisions when decision-making on the behalf of others than for ourselves, which has practical implications in the field of interpersonal conflicts and social dilemmas. However, it remains unclear whether Solomon’s paradox exists across cultures, and the magnitude of its effect size. A meta-analysis was conducted, examining six studies and 20 effect sizes, to gain more insight into this phenomenon, considering the influencing effects of culture, measurement instrument, conflict type, and some other moderating factors. The results showed that Solomon’s paradox does exist in interpersonal conflict (d = 0.317; 95% CI = 0.828 to 0.852). Moderator analysis revealed that measurement instrument and subjects had an impact on the effect of Solomon’s paradox and there was a non-significant effect size of culture and conflict type. Future research should explore the diverse forms of Solomon’s paradox across more diverse cultural contexts (e.g., various countries) to better understand the phenomenon and help people cope with life's problems more wisely.